(untitled) (Journal of Bhuwanishankar, 2023)
The current study explores the impact of behavioral biases such as market factors, herding behavior and awareness factors on investors’ decision-making on the Nepal Stock Exchange and also investigates the mediating role of investors’ sentiment in the relationship among the variables. To comprehend investor sentiment (IS) and how individual investors make decisions, this study introduced an innovative conceptual framework incorporating herding behavior, market dynamics, and awareness factors. A quantitative methodology was used to conduct the investigation, specifically employing a survey research design. This study made use of primary data that was collected by means of a structured questionnaire and gathered data from 408 individual investors. The convenience sample method was used, while structural equation modeling was used as a statistical tool to test hypothesis. It was determined how the market factor, herd behavior, and awareness affect investors’ sentiment and decision-making by using structural equation modeling. The result showed that the most notable factors that affect investors’ sentiment were herding factors. Similarly, in the absence of a moderating variable, investors’ sentiment is affected by all variables, including market factors, herding behavior, and awareness factors which have a significant impact on investors decision-making in the Nepal Stock Exchange. This study aims to assist individual investors in Nepal by guiding their investment choices and preventing sentiment-driven errors. It emphasizes the importance of understanding fellow investors’ sentiment and suggests that awareness programs can enhance market understanding. Previous research has typically examined only a few factors at a time. This current study explores how various factors affecting investor sentiment—like market factors, herding behavior, and awareness—impact investment decision-making among individual investors in Nepal. Importantly, these factors have never been studied together in the context of how Nepalese individual investors make decisions about their investments.